2021
DOI: 10.1002/cctc.202100914
|View full text |Cite
|
Sign up to set email alerts
|

Carbene B−H Insertion Reactions for C−B Bond Formation

Abstract: Carbene BÀ H insertion reactions represent an efficient method for CÀ B bond formation, which have experienced great advances in recent years. Free and metal carbene insertion into BÀ H bonds based on diazo and nondiazo carbene precursors, including α-diazoesters, α-diazoketones, hydrazones, chloroforms, acylsilanes, alkenyl triflates, alkynes and sulfoxonium ylides have been well studied. The development of this chemistry complements existing CÀ B bond formation strategies in terms of substrate scope, selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 58 publications
0
9
0
1
Order By: Relevance
“…Organic boron compounds are widely used in organic synthesis, medicine, and materials science . The synthesis of chiral organoboron compounds has attracted considerable attention, and a number of enantioselective methods have been established . However, although chiral propargylic boron compounds (in which the boron atom is directly connected to the propargylic carbon chiral center) contain easily transformable alkynyl and boron moieties and thus have high potential utility, the synthesis of these compounds remains a significant challenge .…”
mentioning
confidence: 99%
“…Organic boron compounds are widely used in organic synthesis, medicine, and materials science . The synthesis of chiral organoboron compounds has attracted considerable attention, and a number of enantioselective methods have been established . However, although chiral propargylic boron compounds (in which the boron atom is directly connected to the propargylic carbon chiral center) contain easily transformable alkynyl and boron moieties and thus have high potential utility, the synthesis of these compounds remains a significant challenge .…”
mentioning
confidence: 99%
“…We began by carrying out a series of control experiments. A deuterium labeling experiment indicated that a B─H insertion (20)(21)(22) process was involved in the transformation (fig. S1A).…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…As for organoboron compounds, several protocols, including the hydroborations of olefins and C-H bond borylations, offer straightforward access to establish B-C bond [ 27 , 28 , 29 ]. In addition to the above-mentioned methods, the insertion of carbene species into the X-H (X = Si, B) bond stands for another highly efficient route to construct Si-C and B-C bonds [ 30 , 31 ]. The past few decades have witnessed the tremendous development of X-H insertions.…”
Section: Introductionmentioning
confidence: 99%